HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP IBU DENGAN KEJADIAN GIZI KURANG PADA BALITA DI WILAYAH KECAMATAN PONTIANAK KOTA - Syarifah, Latifah; Mardjan, Mardjan; Budiastutik, Indah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
Cases of malnutrition among children under five in Pontianak Pontianak City are in the district. Based on preliminary surveys conducted by researchers to 4 (four) mothers who have children in the District of Pontianak City, that there are several factors that can affect the nutritional status of children, such as not giving breast milk as a baby by (50%), lack of proper feeding (75 %) and do not go to health care (50%). Design of the research conducted in observational analytic survey with cross sectional approach. Large samples are 129 people. The data obtained are presented in narrative form and tabulating. Data analysis with univariate and bivariate analysis with statistical test Chi Square. The results showed an association between maternalknowledge (p value = 0.004 and PR = 1.682), maternal attitude (p value = 0.024 and PR = 1.570) with the incidence of malnutrition among children under five in the Regional District of Pontianak City.Keyword : Knowledge, Attitude, Nutrition Less, Toddler, Mom, District ofPontianak City